Role of ARHGAP29 nucleotide variants in the etiology of non-syndromic cleft lip with or without cleft palate. - Dąbrowska, Justyna; Biedziak, Barbara; Lasota, Agnieszka; Jagodziński, Paweł P.; Mostowska, Adrianna (Journal of Medical Science, 2020)
Aim. Non-syndromic cleft lip with or without cleft palate (nsCL/P) is a common birth defect of complex and heterogeneous aetiology. Genome-wide association studies (GWAS) of nsCL/P have identified an association for the 1p22.1 chromosomal region, in which ARHGAP29 was suggested as a candidate gene. Thus, the current study aimed to determine the contribution of the common and rare ARHGAP29 nucleotide variants to the risk of nsCL/P in the Polish population. Material and Methods. In total,197 common nucleotide variants (SNVs) and 22 missense variants located within the ARHGAP29 locus at chromosome 1p22.1 were genotyped by SNV microarray. The study was conducted in 269 individuals with nsCL/P and 569 healthy individuals. Results. Statistical analysis revealed that 31 common nucleotide variants located at the ARHGAP29 locus were significantly associated with the increased risk of nsCL/P. The strongest individual SNV was rs2391467 with a p-value = 2.49E-06 (OR = 1.64, 95%CI: 1.34–2.02). Besides, one potentially deleterious missense variant (rs140877322, p. Arg348Leu) was identified in a single patient with nsCLP. Conclusion. These findings confirm ARHGAP29 as a strong candidate gene for nsCL/P, with both common and rare nucleotide variants of this gene involved in the aetiology of nsCL/P in the Polish population.